Use of Rapid Antigen Detection Tests Versus Viral Culture in De-isolation Decision-Making for Critically Ill Patients Infected with Omicron B.1.1.529 - Abeer N. Alshukairi; Ashraf Dada; Yasser Aldabbagh; Mohammed F. Saeedi; Sherif A. El-Kafrawy; Ahmed M. Hassan; Thamir A. Alandijany; Mohammad K. Al Hroub; Basem M. Alraddadi; Imran Khalid; Ghadeer E. Albishi; Mohammed Qutub; et al. (Dr. Sulaiman Al Habib Medical Journal)
Background COVID-19 vaccination effectively decreased hospitalization and mortality during the surge of infections with the SARS-CoV-2 Omicron variant. However, patients infected with the Omicron variant who did not receive a third COVID-19 vaccine booster often required critical care unit (CCU) admission. The CCU bed utilization of COVID-19 posed a worldwide burden. The decision to stop isolation of patients with COVID-19 in CCUs is challenging, given the variable viral shedding in heterogeneous patient populations. Rapid antigen detection tests (RADTs) have been used in communities to determine patients' infectiousness and need for quarantine. However, the use of RADTs in the de-isolation of CCU patients had not been studied. Methods Serial RADTs, RT-PCR and viral culturing were performed in a case series of three critically ill patients infected with Omicron variants. Results The duration of infectious viral shedding was 13–46 days post symptom onset (PSO). Concordant negative results were observed between RADTs and viral cultures on D32 PSO in case 1; D13 and D15 PSO in case 2; and D46 and D48 PSO in case 3. In addition, concordant positive results were found between RADTs and viral cultures on D35 PSO in case 2. Significant agreement was observed between RADT and viral culture findings (kappa statistic = 1.0 and p-value = 0.014). Conclusion Given their high positive predictive value with respect to positive viral cultures, RADTs may be a promising and practical tool for ending isolation of patients with COVID-19 and decreasing the burden of CCU bed utilization. Future studies are necessary to confirm our findings.